3D-fabrication of tunable and high-density arrays of crystalline silicon nanostructures. (15th February 2018) - Wilbers, J G E; Berenschot, J W; Tiggelaar, R M; Dogan, T; Sugimura, K; van der Wiel, W G; Gardeniers, J G E; Tas, N R
Abstract: In this report, a procedure for the 3D-nanofabrication of ordered, high-density arrays of crystalline silicon nanostructures is described. Two nanolithography methods were utilized for the fabrication of the nanostructure array, viz. displacement Talbot lithography (DTL) and edge lithography (EL). DTL is employed to perform two (orthogonal) resist-patterning steps to pattern a thin Si3 N4 layer. The resulting patterned double layer serves as an etch mask for all further etching steps for the fabrication of ordered arrays of silicon nanostructures. The arrays are made by means of anisotropic wet etching of silicon in combination with an isotropic retraction etch step of the etch mask, i.e. EL. The procedure enables fabrication of nanostructures with dimensions below 15 nm and a potential density of 10 10 crystals cm −2 .